Hypnobirthing and Prenatal Yoga on Pain and Labor Duration: Literature Review - Anggrita Sari, Siti Sarah Citra Hati, R. Topan Aditya Rahman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pregnancy and childbirth are natural processes expected to become subconsciously-recorded experiences, which affects the pain and duration of labor. Hypnobirthing and prenatal yoga as alternative non-pharmacological methods for a complementary alternative for pregnant women holistically (body, mind, soul) are considered adequate to reduce pain and duration of labor. However, few have adopted and researched the combination of the two methods. Aim: To examine research articles on the effectiveness of hypnobirthing and prenatal yoga on pain and duration of labor. Methods: This study used a literature review using journals or articles selected based on predetermined criteria. Eight out of 11 reports concluded that hypnobirthing effectively reduced pain and duration of labor, while three articles had the opposite result. Ten articles on prenatal yoga discovered its effectiveness in reducing pain and time of labor. Meanwhile, one combined report on hypnobirthing and prenatal yoga showed their efficacy to reduce labour duration. Conclusion: Hypnobirthing and prenatal yoga effectively reduce pain and duration of labor for the first, second, and third stages mothers with appropriate application standards. The combination of Hypnobirthing and Prenatal Yoga is necessary to obtain maximum results.